Characterization, evolution and risk factors of diabetes and prediabetes in a pediatric cohort of renal and liver transplant recipients - Sophie Welsch; Virginie Mailleux; Priscilla le Hardy de Beaulieu; Nadejda Ranguelov; Nathalie Godefroid; Annie Robert; Xavier Stephenne; Isabelle Scheers; Raymond Reding; Etienne M. Sokal; Etienne M. Sokal; Philippe A. Lysy; et al. (Frontiers Media S.A., 2023)
BackgroundHyperglycemia (HG) and prediabetes are rarely sought in pediatric liver (LT) and renal (RT) transplantation, yet their presence indicates a high risk of diabetes and cardiovascular disease. The objectives of our DIABGRAFT study were to retrospectively (rDIABGRAFT) and longitudinally (pDIABGRAFT) characterize HG and (pre)diabetes in a cohort of children with LT or/and RT.MethodsWe retrospectively analyzed risk factors of HG from 195 children with LT from 2012 to 2019 and twenty children with RT from 2005 to 2019 at Cliniques universitaires Saint-Luc. In addition, we prospectively followed four LT and four RT children to evaluate the evolution of their glucose metabolism.ResultsOur rDIABGRAFT study showed that 25% and 35% of LT and RT children respectively presented transient HG and 20% of RT developed diabetes. The occurrence of HG was associated with the use of glucocorticoids and with acute events as graft rejection and infection. In our pDIABGRAFT cohort, biological markers of diabetes were in the normal range for HbA1C, fasting glucose and insulin levels. However, oral glucose tolerance test and glucose sensors showed insulin resistance, impaired glucose tolerance and HG in the post-prandial afternoon period.ConclusionOur study shows that children with LT and RT were more at risk of developing HG when glucocorticoids were required and that HbA1C and fasting glucose lack sensitivity for early detection of glucose intolerance. Also, measurement of glycemia immediately after the transplantation and in postprandial period is key to detect dysglycemia since insulin resistance prevailed in our cohort.ClinicalTrials.gov IDNCT05464043.